Letter (copy) : Ana Maria Gallut Fernandez - Tewson, Vincent
1939-07-17 038-0080-003 -2- in your letter, but in the face of the expressed request of Mr. Gallut to Mrs. Curtis our hands were tied, and we had to leave the matter as it had been dealt with by Mrs. Curtis. Yours sincerely, Assistant Secretary. 292/946/38/80(III)